1997
DOI: 10.1038/sj.onc.1201440
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2-dependent phosphorylation of p27 facilitates its Myc-induced release from cyclin E/cdk2 complexes

Abstract: Activation of Myc triggers a rapid induction of cyclin E/ cdk2 kinase activity and degradation of p27. Overt degradation of p27 is preceded by a speci®c dissociation of p27 from cyclin E/cdk2, but not from cyclin D/cdk4 complexes. We now show that cyclin E/cdk2 phosphorylates p27 at a carboxy-terminal threonine residue (T187) in vitro; mutation of this residue to valine stabilises cyclin E/cdk2 complexes. This reaction is not signi®cantly inhibited by high concentrations of p27, suggesting that cdk2 bound to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
125
2
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 44 publications
14
125
2
1
Order By: Relevance
“…For example, a Myc-regulated heat-labile inhibitor of p21 has been described (20). By an apparently similar mechanism, in cells which express abundant p27 but little p21, Myc induction inhibits the ability of p27 to bind cyclin E-Cdk2, most likely by causing the p27 to be sequestered (34,41,62). While cyclin D-Cdk4 or cyclin D-Cdk6 complexes provide an attractive possibility for the sequestration of p27 or p21, increased association between these proteins and p27 was not observed following c-Myc induction (62).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, a Myc-regulated heat-labile inhibitor of p21 has been described (20). By an apparently similar mechanism, in cells which express abundant p27 but little p21, Myc induction inhibits the ability of p27 to bind cyclin E-Cdk2, most likely by causing the p27 to be sequestered (34,41,62). While cyclin D-Cdk4 or cyclin D-Cdk6 complexes provide an attractive possibility for the sequestration of p27 or p21, increased association between these proteins and p27 was not observed following c-Myc induction (62).…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, data from this laboratory suggest that following c-Myc induction in human breast cancer cells, p21 and p27 are not sequestered by cyclin D-Cdk4 (43). Recent data suggest that the sequestered p27 is targeted for degradation, raising the possibility that the sequestering proteins are involved in the degradation process (34). It is possible that the decrease in c-myc expression following progestin treatment results in decreased expression of p21-and p27-sequestering molecules, contributing to increased availability of p21 and p27 for cyclin-CDK binding.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, regulation of p27 Kip1 protein degradation seems to be the most important mechanism by which this important CKI is regulated. It is known that p27 Kip1 degradation occurs via ubiquitination ( [92]; reviewed in [93]), because p27 Kip1 is phosphorylated on Thr 187 by Cdk2/cyclin E and this phosphorylated form is then targeted for ubiquitination and degradation [94][95][96][97]. Pagano and coworkers [98] demonstrated that ubiquitination of p27 Kip1 requires prior phosphorylation of p27 Kip1 on Thr187 as well as trimeric complex formation among p27 Kip1 , Cdk2 and cyclin A or E. As expected, proteasome inhibitors lead to p27 Kip1 accumulation [99].…”
Section: Cdc25a Phosphatasementioning
confidence: 99%
“…For example, induction of c-MycER fusion protein by 4-OH tamoxifen in Rat1 fibroblasts leads to Cdk2/cyclin E activation. This is a result of: i) inhibition of p27 Kip1 binding to the Cdk2/cyclin E complexes [104], ii) p27 Kip1 release from the Cdk2/cyclin E complexes [97], and iii) p27 Kip1 degradation [105]. Furthermore, retroviral expression of p27 Kip1 induces G1 arrest in parental Rat1 cells, but not in Rat1 cells that ectopically express c-Myc [106].…”
Section: Cdc25a Phosphatasementioning
confidence: 99%
“…Whereas P27 needs to be transported into the nucleus to exert its effect on the cell cycle (30), degradation of p27 by a ubiquitin-dependent pathway requires cytoplasmic localization of p27 (31,32). Thus, the next question that we addressed was the role of Rac1 on the Ang II-induced nuclear translocation of p27.…”
Section: Modulatory Effect Of Smv On Ang Ii-induced Rac1 Activationmentioning
confidence: 99%